2016
DOI: 10.1088/1757-899x/124/1/012132
|View full text |Cite
|
Sign up to set email alerts
|

Formation of intermetallics at the interface of explosively welded Ni-Al multilayered composites during annealing

Abstract: Abstract. The Ni-Al multilayer composite was fabricated using explosive welding. The zones of mixing of Ni and Al are observed at the composite interfaces after the welding. The composition of these zones is inhomogeneous. Continuous homogeneous intermetallic layers are formed at the interface after heat treatment at 620 °C during 5 h. These intermetallic layers consist of NiAl 3 and Ni 2 Al 3 phases. The presence of mixed zones significantly accelerates the growth rate of intermetallic phases at the initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
2
12
0
Order By: Relevance
“…This observation is inconsistent with the presented work, where arrangement of the colliding plates always led to the wavy nature of the area of joining; however, these waves were significantly broader, when the aluminum alloy acted as a flyer plate. Nevertheless, the same microstructure components inside the waves such as fine dendrites or vortex were observed as in [18,19]. Chemical composition measurements confirmed that the melted zones were not homogeneous and consisted of a mixture of Al and Ni with various concentrations of these elements; however, the analytical resolution of EDS in SEM is insufficient for fine-grained regions as well as the swirled ones and for revealing the type of possible intermetallic phases existing in the melted regions.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…This observation is inconsistent with the presented work, where arrangement of the colliding plates always led to the wavy nature of the area of joining; however, these waves were significantly broader, when the aluminum alloy acted as a flyer plate. Nevertheless, the same microstructure components inside the waves such as fine dendrites or vortex were observed as in [18,19]. Chemical composition measurements confirmed that the melted zones were not homogeneous and consisted of a mixture of Al and Ni with various concentrations of these elements; however, the analytical resolution of EDS in SEM is insufficient for fine-grained regions as well as the swirled ones and for revealing the type of possible intermetallic phases existing in the melted regions.…”
Section: Resultsmentioning
confidence: 65%
“…In respect to previous works about EXW of Al/Ni system, the current paper demonstrates how the interface develops with respect to the various localizations of the colliding plates (aluminum alloy acts either as a flyer plate or base plate). The authors of previous reports [18,19] concluded that the influence of the arrangement of the colliding plates is not significant; however, the discrepancies regarding the localization of the plates could be noticed as can be seen in figure in the work [18]. A similar observation was made by Fronczek et al [1,20], where Ti Gr.2 and Al 1050 were explosively welded.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations